A Review of Hybrid Process Development Based on Electrochemical and Advanced Oxidation Processes for the Treatment of Industrial Wastewater. (8th August 2022) - Asaithambi, Perumal; Yesuf, Mamuye Busier; Govindarajan, Rajendran; Hariharan, N.M.; Thangavelu, Perarasu; Alemayehu, Esayas
Abstract : Nowadays, increased human activity, industrialization, and urbanization result in the production of enormous quantities of wastewater. Generally, physicochemical and biological methods are employed to treat industrial effluent and wastewater and have demonstrated high efficacy in removing pollutants. However, some industrial effluent and wastewater contain contaminants that are extremely difficult to remove using standard physicochemical and biological processes. Previously, electrochemical and hybrid advanced oxidation processes (AOP) were considered a viable and promising alternative for achieving an adequate effluent treatment strategy in such instances. These processes rely on the production of hydroxyl radicals, which are highly reactive oxidants that efficiently break down contaminants found in wastewater and industrial effluent. This review focuses on the removal of contaminants from industrial effluents and wastewater through the integration of electrochemical and advanced oxidation techniques. These processes include electrooxidation, electrocoagulation/electroflocculation, electroflotation, photo-Fenton, ozone-photo-Fenton, sono-photo-Fenton, photo-electro-Fenton, ozone/electrocoagulation, sono-electrocoagulation, and peroxi/photo/electrocoagulation. The data acquired from over 150 published articles, most of which were laboratory experiments, demonstrated that the hybrid process is more effective in removing contaminants from industrial effluent and wastewater than standalone processes.